Early real-world evidence of persistence on oral anticoagulants for stroke prevention in non-valvular atrial fibrillation: a cohort study in UK primary care. Issue 9 (26th September 2016) - Johnson, Michelle E; Lefèvre, Cinira; Collings, Shuk-Li; Evans, David; Kloss, Sebastian; Ridha, Essra; Maguire, Andrew
Abstract : Objectives: To examine the characteristics and persistence in patients newly initiated with oral anticoagulants (OACs) for stroke prevention in non-valvular atrial fibrillation (NVAF). Design: Cohort study in Clinical Practice Research Datalink. Setting: UK primary care. Participants: 15 242 patients with NVAF newly prescribed apixaban, rivaroxaban, dabigatran or vitamin K antagonists (VKAs) between 1 December 2012 and 31 October 2014. 13 089 patients were OAC naïve. Outcome measures: Patient characteristics and risk of non-persistence compared to apixaban using Cox regression models over the entire follow-up and using a time-partitioned approach to handle non-proportional hazards. Results: Among the OAC naïve patients, VKAs were most common (78.1%, n=10 218), followed by rivaroxaban (12.1%, n=1589), dabigatran (5.7%, n=741) and apixaban (4.1%, n=541). High baseline stroke risk (CHA2 DS2 VASc ≥2) ranged from 80.2% (dabigatran) to 88.4% (apixaban and rivaroxaban). History of stroke and bleeding was the highest among apixaban (23.7% and 31.6%) and lowest among VKA patients (15.9% and 27.5%). Across the entire follow-up period, adjusting for differences in characteristics, there was no evidence of a difference in non-persistence between VKA and apixaban (HR 0.92 (95% CI 0.68 to 1.23)). Non-persistence was higher with dabigatran (HR 1.67 (1.20 to 2.32)) and rivaroxaban (HR 1.41 (1.02 to 1.93)) than apixaban. Using the partitioned approach, non-persistence was lower with VKA (HR 0.33 (0.22 to 0.48)), and higher with dabigatran (HR 1.65 (1.08 to 2.52)) compared to apixaban in the first 2 months of follow-up. After 2 months, non-persistence was higher with VKA (HR 1.70 (1.08 to 2.66)) and dabigatran (HR 2.10 (1.30 to 3.41)). Pooling OAC naïve and experienced patients, non-persistence was also higher with rivaroxaban compared to apixaban after 2 months of follow-up (HR 1.69 (1.19 to 2.39)). Conclusions: Observed differential prescribing of OACs can result in channelling bias in comparative effectiveness research. Persistence patterns changed over follow-up time, but there are indications of improved persistence rates with apixaban over other OACs in the UK. A larger study with longer follow-up is needed to corroborate findings. This study is registered on ClinicalTrials.gov (NCT02488421 ).